A 38-plex PCR MALDI-TOF MS-based assay to detect SNPs common in elite athletes - Miftahul Zannah; Ioannis Papadimitriou (PLoS ONE, 2025)
There is great demand for a novel technique to facilitate the rapid identification of multiple single-nucleotide polymorphisms (SNPs) prevalent in elite athletes. Case-control and genome-wide association studies (GWAS) have been conducted to investigate an individual’s likelihood for success in various sports, revealing several putative loci associated with elite athletic status. However, it remains challenging to detect multiple such SNPs simultaneously with the aim of examining their influence on specific physical fitness characteristics, such as muscle power, strength, or endurance. The aim of the present study is to develop a 38-plex PCR amplification assay, integrated with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), for the identification of 38 SNPs linked to elite athletic performance and assess its quantitative performance metrics and high-throughput capabilities within a single 38-plex reaction. The SNPs were chosen based on their high prevalence among elite power athletes, potential influence on muscle power production, and suitability for multiplex PCR amplification. The developed method simultaneously detected the targeted SNPs in a single tube, using a minimum DNA concentration of 10 ng/μL and achieving a total sample call rate of 93.13%. With further research, this new protocol—which integrates the specificity of multiplex PCR and the sensitivity of MALDI-TOF MS—may offer a unique opportunity to deepen our understanding of the genetic basis of physical fitness and may have prospective applications in research initiatives exploring genetic factors that influence athletic performance, e.g., the Speed Gene Study.